Production of anti-tumor l- asparaginase by free and immobilized marine cyanobacterium phormidium Formosum as a novel source - REHAM G. ELKOMY; AIDA M. FARAG (International Journal of Pharma and Bio Sciences, 2018)
L-asparaginase (L-AsnA) is cosmopolitan among microorganisms and has vital applications in medical and in food technology sectors. Therefore, the power of the assembly, of L-AsnA from Phormidium formosum was tested. Cyanobacterium Phormidium formosum were isolated from Eastern harbor of Mediterranean Sea coast of Alexandria, Egypt. Different incubation temperatures ranged from 20°C to 45°C were applied to get the optimum incubation temperature for the enzyme production using modified F/2 medium. The pH range between pH 6.0 to 10.0 was applied on the modified F/2 production medium to demonstrate the optimum pH for L-asparaginase production. Adsorption of Phormidium formosum on different solid porous supports such as pumice, coal, ceramic, luffa pulp and polyurethane foam for l-asparaginase production was investigated. Phormidium formosum cultures were grown in F/2 medium for 14th days. The cultures of Phormidium formosum showed a high L-AsnA enzyme activity (49.120 U/ml). the optimized pH and temperature were 8 and 30 oC, respectively. Immobilization using adsorbed Luffa pulp enhanced the enzyme production compared to the conventional free- cells repeated reuse of the adsorbed cells and achieved the maximum enzyme specific activity (52.562U/ml). Scans using electron microscopic showed the adsorption of P. formosum on the pores of luffa pulp. The study findings revealed that Phormidium formosum can provide a new and rich source of L-asparaginase enzyme and this can be the primary report on L-asparaginase production P. formosum.